The results of field studies of the stress-strain state steel-reinforced concrete span structure of the railway bridge - Hernich, M. V.; Kliuchyk , S. V. (Science and Transport Progress, 2022)
Purpose. The purpose of the study was to determine the stress-strain state and operating characteristics of the existing steel-reinforced-concrete span structure under the railway after long-term operation under static and dynamic loads. Methodology. To achieve the goal, full-scale surveys of the existing bridge crossing were carried out, more attention was focused on the steel-reinforced concrete span structure, the conditions and features of its operation were determined, and static and dynamic tests were conducted. During the tests, the general deformations of the span structures (vertical and horizontal deflections) and the stress state in the elements of the structures under different load schemes were measured. During dynamic tests, registration of static and dynamic component deflections and stress changes in structural elements during the passage of rolling stock along the span structure was carried out. The interaction of the span structure with the rolling stock, the influence of uneven approaches to the bridge on the excitation of the rolling stock was investigated. Findings. The values of stresses in the elements of the steel-reinforced-concrete span structure were obtained when the test load was installed in the position at which the greatest stresses and deformations should occur in the test elements, the frequencies of natural and forced oscillations of the span structure were measured, the dynamic coefficient, the dynamic deflections of the main beams were determined, the values decrements of oscillations of the frequency of natural and forced oscillations. The dynamic interaction of the rolling stock with the steel-reinforced concrete span structure was studied. Analytical assumptions in the design of steel-reinforced-concrete span structures of bridges have been confirmed. Originality In the work, a study of the stress-deformed state of the steel-reinforced concrete span structure of the railway bridge after long-term operation, the simultaneous operation of the span structure with rolling stock was carried out. Practical value. The operating conditions of the steel-reinforced-concrete span structure of the railway bridge, static and dynamic characteristics of its operation, the interaction of the rolling stock with the span structure, the influence of the unevenness of the approach track to the bridge on the dynamic interaction of the span structure and the rolling stock are determined. Practically confirmed analytical calculations of deformation and dynamic characteristics of steel-reinforced-concrete span structures of bridges, the joint operation of steel beam and reinforced concrete slab is ensured to a sufficient extent and corresponds to theoretical assumptions.